2003
DOI: 10.1073/pnas.0235749100
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the MurG:UDP-GlcNAc complex reveals common structural principles of a superfamily of glycosyltransferases

Abstract: MurG is an essential glycosyltransferase that forms the glycosidic linkage between N-acetyl muramyl pentapeptide and N-acetyl glucosamine in the biosynthesis of the bacterial cell wall. This enzyme is a member of a major superfamily of NDP-glycosyltransferases for which no x-ray structures containing intact substrates have been reported. Here we present the 2.5-Å crystal structure of Escherichia coli MurG in complex with its donor substrate, UDPGlcNAc. Combined with genomic analysis of other superfamily member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
236
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(257 citation statements)
references
References 35 publications
16
236
0
Order By: Relevance
“…This result is, again, in good agreement with the concluded role of NDP on SpnG. In contrast, previous studies reported that MurG accepted only an UDP-sugar, and vancomycin group Gtfs utilized both UDPand TDP-sugars (26,40). For the discrimination between UDPsugar and TDP-sugar, a Glu residue was observed in MurG to hydrogen-bond to the ribose 2Ј-and 3Ј-hydroxyls, whereas in vancomycin group Gtfs a replacement with Val or Leu was found (25), forming no hydrogen bond.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This result is, again, in good agreement with the concluded role of NDP on SpnG. In contrast, previous studies reported that MurG accepted only an UDP-sugar, and vancomycin group Gtfs utilized both UDPand TDP-sugars (26,40). For the discrimination between UDPsugar and TDP-sugar, a Glu residue was observed in MurG to hydrogen-bond to the ribose 2Ј-and 3Ј-hydroxyls, whereas in vancomycin group Gtfs a replacement with Val or Leu was found (25), forming no hydrogen bond.…”
Section: Discussionsupporting
confidence: 72%
“…Ribbon representation of ␣␤␣ motif in MurG, GtfA, GtfB, GtfD, and SpnG. The ␣␤␣ motif structures of MurG, GtfA, GtfB, and GtfD are known as reported (23)(24)(25)(26), whereas that of SpnG was generated in this study by SWISS-MODEL with GtfB as a template (43) (available on the World Wide Web). The conserved ␣␤␣ motif is proposed to be involved in the binding of NDP-sugar and exhibits similar folding in these five glycosyltransferases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of resistance to ␤-lactams and other clinically used antibiotics has prompted intense interest in understanding peptidoglycan biosynthesis in detail. Major advances have been made in recent years with respect to the characterization of key biosynthetic enzymes (3)(4)(5). Several structures have been reported for enzymes that catalyze transpeptidation (6,7), but no PGT structures have been described.…”
mentioning
confidence: 99%